A Seamless Switching Strategy for Hybrid AC/DC Microgrids Under Varied Control Complexities - Huayu Zhang; Shan He; Zhi Yuan; Zhijiang Cheng; Jing Cheng; Bing Hu; Lijun Xu; Xiaochao Fan (IEEE Access)
In peer-to-peer controlled hybrid AC/DC microgrids, the grid-connected inverters switch between different control modes with the change of the operating conditions. However, the above-mentioned mode transitions trigger transient disturbances in voltage, frequency, and current, causing power mismatch, such that the smooth operation of the microgrid will be hampered. To solve the above-mentioned problems, a composite control strategy is proposed in this study following droop control and PQ control, with the aim of achieving seamless switching between islanded and grid-connected modes. The proposed strategy couples the current inner loops of the above control methods (droop control and PQ control) to develop a dual-mode combined controller operating based on current tracking. This configuration enables the reference current of the input current inner loop controller to track the pre-switching state while maintaining the correct initial value. Moreover, a compensatory pre-synchronization control strategy is developed to cope with variations in frequency, phase, and amplitude. The voltage offset is improved from 19% to synchronize with the grid, and the microgrid islanded/grid-connected mode is smoothly switched. The reference value of the outer loop is changed by PQ control, so that the exchange power of the grid side and the microgrid side is 0. Thus, seamless switching between grid-connected and islanded modes can be achieved. The effectiveness and feasibility of the control strategy proposed in this study are verified in the simulation system.